A novel and efficient technology of depositing Al2O3 film for OLEDs thin film encapsulation. (February 2022) - Yuan, Heng; Li, Qian; Yan, Weiqing; Zhang, Yifan; Chen, Lin; Pan, Pang; Luo, Jun; Liao, Bin; Ouyang, Xiaoping
Abstract: Organic light-emitting diode devices (OLEDs) industry is developing rapidly, however, OLEDs are very sensitive to oxygen and water, determining how to achieve better barrier effect is one of the main challenges of flexible OLEDs technology. Based on the filtered cathode vacuum arc (FCVA) technology, a dense aluminum oxide (Al2 O3 ) film with a thickness of about 100 nm was grown at room temperature for OLEDs encapsulation. The composition, structure, surface roughness, refractive index, light transmittance and other physical properties of the film were analyzed. The water vapor transmission rates (WVTRs) of the films were tested at 85 °C and 85% relative humidity (R.H.). Photoluminescence spectrum (PL) test was carried out to study the luminescence ability of tris(8-hydroxyquinoline) aluminum (Alq3 ) before and after the deposition of Al2 O3 film. The results show that the amorphous Al2 O3 film with dense structure prepared by FCVA has high visible light transmittance. The Al2 O3 film reduces the WVTRs of the polyethylene naphthalate (PEN) film by four orders of magnitude and maintains the light-emitting performance of the organic light-emitting layer. These results indicate that the FCVA technology is a feasible method for preparing barrier films of flexible OLEDs. Highlights: The FCVA is applied to the field of OLEDs encapsulation. Rapidly deposited Al2 O3 (15 nm/min) by FCVA do not reduce PL intensity of Alq3 . Al2 O3 film with 100 nm thickness reaches low WVTRs value of 9.897 × 10 −4 g/m 2 /day.